Engineering for industrial designers and inventors : how to design wonderful things (O'Reilly, 2016)
"Having a visceral understanding of mechanical engineering is key to effectively designing industrially manufactured products and systems. Without it, the products you create may bend and break. But many creative designers find it difficult to develop that foundational awareness due to the plodding math-centric method by which mechanical engineering is usually taught. Twenty year industrial design veteran Thomas Ask breaks free from that constrained approach by offering food to both sides of the brain in this holistic look at how to design wonderful things. Ask, a founder of the Society of Inventors and Mad Scientists, feeds the right brain first with a rich survey of the non-technical influences (cultural traditions, visual stereotypes, brand management, etc.) that propel or inhibit industrial design. Then it's the left brain's turn, with a deep chew into material mechanics, heat transfer, and fluid dynamics (the core disciplines of mechanical engineering), where Ask's specially prepared found-in-nature examples helpfully flavor each topic."--Resource description page.